2020
DOI: 10.1016/j.jcorpfin.2019.101503
|View full text |Cite
|
Sign up to set email alerts
|

Herd behaviour in buyout investments

Abstract: In this study, we explored the presence of correlated investment choices (i.e., herd behaviour) among international buyout funds by distinguishing among the contemporaneous and the following herding of smaller funds towards the top market players (i.e., the top quartile in terms of the fund size). In our analyses, we found that the industry herding towards the largest ones is common in private equity (PE) but mostly during market contractions or the deterioration of general market conditions. Moreover, we also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition, institutional investors also use LPE as a complement to their traditional (unlisted) private equity investment strategy (Huss and Zimmermann, 2012). Moreover, institutional investors often herd (Lakonishok et al , 1992; Buchner et al , 2020), i.e. they invest in similar assets at the same time, which leads to similar strategies and thus similar outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, institutional investors also use LPE as a complement to their traditional (unlisted) private equity investment strategy (Huss and Zimmermann, 2012). Moreover, institutional investors often herd (Lakonishok et al , 1992; Buchner et al , 2020), i.e. they invest in similar assets at the same time, which leads to similar strategies and thus similar outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Firms should pay more attention to peer effects in capital structure and become more cautious with their imitation in capital structure adjustments because peer effects in capital structure will affect corporate development. Some prior studies on peer effects in firms'financial decisions have concluded that peer effects are beneficial for firms because they can help obtain more information and experience from peers (Buchner et al, 2020;Tian et al, 2021), while others argue that it is detrimental because firms might imitate their peers without considering their characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to increased demand for assets within that industry, which can drive up prices and boost gains in short period of time. Buchner et al (2019), similarly Sehgal and Jain (2015) talked the momentum effect, proposing its origin in both behavioural and rational sides. The Indian stock market exhibits a momentum effect that traditional risk models fail to summarize fully, hinting at behavioural factors.…”
Section: Behavioural Factors In Financementioning
confidence: 99%